Sunlight‐Driven Synthesis of Triarylethylenes (TAEs) via Metal‐Free Mizoroki–Heck‐Type Coupling. Issue 38 (23rd August 2018) - Onuigbo, Louis; Raviola, Carlotta; Di Fonzo, Andrea; Protti, Stefano; Fagnoni, Maurizio
Abstract : A protocol for the preparation of substituted triarylethylenes (TAEs) was developed by using arylazo sulfones as substrates in the presence of 1, 1‐diarylethylenes. The process took place efficiently in the absence of any (photo)catalyst upon exposure of the reaction mixture to (simulated) sunlight. Abstract : The preparation of substituted triarylethylenes (TAEs) was achieved under metal‐ and (photo)catalyst‐free conditions, starting from photoactivated arylazo sulfones.